Reflections of Servant Leadership from Great Epics of India - G. , Anupama; Agarwal, Padmavathi (International Journal of Psychosocial Rehabilitation, 2020)
The leadership styles as per the Western research are charismatic, benevolent, democratic, transactional, transformational, participative, free-reign, laissez-faire, etc. The basic models are drawn from the corporate fields and setups where individuals come together, work, and contribute to the accomplishment of common objectives. Many studies identified the servant leadership style to be the more reliable and result-oriented style in organizational arenas. But the reflections of servant leadership are encrypted in the famous epics of India. The qualities of characters such as Krishna from Mahabharata, Rama from Ramayana, Bharatha from Ramayana, and the role of the Pandavas in Mahabharata during their period of exile stand as examples of the servant leadership style. The present study makes an attempt to find out whether these replications of servant leadership values drawn from the great epics are represented by managers at workplaces. The results indicate that there are no significant reflections of great epics on the specific values drawn from them by the managers, but there is a significant impact of epic values on their personal values. These further have their influence on the servant leadership values of the managers in organizations. The socio-demographic factors have no significant influence on the managers’ epic values but have a significant impact on the managers’ personal values. The present research has immense scope for future research on great epics of India from which many corporate culture and value-based inputs can be drawn. It is expected that these popular epics extend many opportunities and guidelines for managers in decision-making and ethical dilemmas and create the best corporate cultures in the business world.